(747) أساسيات لغة الفورتران (الجزء الأول) Fortran Language Basics (Part 1) - رمضان عبد المعطى محمد (معهد التخطيط القومي, 2026)
المذكرة دليلاً أساسياً لتعلم لغة البرمجة "فورتران" (FORTRAN). يبدأ الملف بمدخل حول اللغات الراقية وتطور الفورتران ومكونات نظامها التي تشمل قواعد اللغة والمحول البرمجي (Compiler)، مع شرح دقيق لهيكل البرنامج وكيفية كتابة الأكواد باستخدام كشوف التعليمات والبطاقات المثقبة، وتوضيح أهمية تقسيم الحقول البرمجية مثل حقل التعليق، ورقم التعليمة، وحيز التكملة، لضمان صياغة برامج خالية من الأخطاء الشكلية والمنطقية.كما تركز على قواعد التعامل مع الثوابت والمتغيرات بأنواعها المختلفة (الصحيحة والعشرية)، وكيفية تنظيم المنظومات أو المصفوفات ذات الأبعاد المتعددة وحجزها في الذاكرة. كما يستعرض الملف التعليمات الحسابية وترتيب تنفيذ العمليات، بالإضافة إلى تعليمات المدخلات والمخرجات التي تسمح بقراءة البيانات وطباعة النتائج بتنسيقات محددة. وينتهي هذا الجزء بشرح تعليمات التحكم والانتقال وحلقات التكرار، مع تقديم أمثلة برمجية عملية تشمل حساب المساحات وحل المعادلات الآنية، مما يوفر أساساً متيناً للمبرمجين للتعامل مع النماذج الرياضية المعقدة. This document serves as an essential guide for learning the FORTRAN programming language. It begins with an introduction to high-level languages ​​and the evolution of FORTRAN, including its system components such as syntax and compiler. A detailed explanation of program structure and how to write code using instruction sheets and punch cards is provided, highlighting the importance of dividing programming fields, such as comment fields, instruction numbers, and extension spaces, to ensure the creation of programs free from formal and logical errors. The document also focuses on handling constants and variables of various types (integers and decimals), and how to organize and allocate multidimensional arrays. Furthermore, it covers arithmetic instructions and the order of operations, as well as input/output instructions that allow for reading data and printing results in specific formats. This section concludes with an explanation of control, traverse, and loop instructions, along with practical programming examples including area calculations and simultaneous equation solving, providing programmers with a solid foundation for working with complex mathematical models.